The Effect of REACT Model Assisted Fable-Math Book Media on Mathematical Problem Solving Of Elementary School Students - Destiana Dian Arfiani; Himmatul Ulya; Savitri Wanabuliandari (MEJ (Mathematics Education Journal), 2020)
This study aims to analyze (1) the average mathematical problem solving ability of students who can achieve the KKM, (2) the proportion of students who can complete classical completeness of 75%, (3) differences in students' mathematical problem solving abilities before and after the REACT model assisted by fable-math book media is applied, (4) increasing mathematical problem solving abilities. The research method used is quantitative research with a pre-experimental design trial design in the form of one group pretest posttest. Sampling was done by means of purposive sample. The sample in this study were IV grade students in academic year 2019/2020. Collecting data using interview techniques, documentation, and tests. The data that has been collected is then analyzed using statistical analysis in the form of one sample t-test, z-proportion test, paired sample t-test, and n-gain test. After applying the REACT model assisted by the fable-math book media the results of the study showed that the average score of the student's problem-solving ability test got more than 70, the proportion of students who completed the test could achieve classical completeness above 75%, there were significant differences in the pretest and posttest results, and there is an increase in students' mathematical problem solving abilities with the medium category.